Determinants of well-being and their interconnections in Australian general practitioners: a qualitative study - Nick Glozier; Ian B Hickie; Christiane Klinner; Alyssa Milton; Diana Naehrig; Louise Acland; Brendan Goodger (BMJ Open)
Objectives The well-being of doctors is recognised as a major priority in healthcare, yet there is little research on how general practitioners (GPs) keep well. We aimed to address this gap by applying a positive psychology lens, and exploring what determines GPs’ well-being, as opposed to burnout and mental ill health, in Australia.Design Semi-structured qualitative interviews. From March to September 2021, we interviewed GPs working in numerous settings, using snowball and purposive sampling to expand recruitment across Australia. 20 GPs participated individually via Zoom. A semi-structured interview-guide provided a framework to explore well-being from a personal, organisational and systemic perspective. Recordings were transcribed verbatim, and inductive thematic analysis was performed.Results Eleven female and nine male GPs with diverse experience, from urban and rural settings were interviewed (mean 32 min). Determinants of well-being were underpinned by GPs’ sense of identity. This was strongly influenced by GPs seeing themselves as a distinct but often undervalued profession working in small organisations within a broader health system. Both personal finances, and funding structures emerged as important moderators of the interconnections between these themes. Enablers of well-being were mainly identified at a personal and practice level, whereas systemic determinants were consistently seen as barriers to well-being. A complex balancing act between all determinants of well-being was evidenced.Conclusions GPs were able to identify targets for individual and practice level interventions to improve well-being, many of which have not been evaluated. However, few systemic aspects were suggested as being able to promote well-being, but rather seen as barriers, limiting how to develop systemic interventions to enhance well-being. Finances need to be a major consideration to prioritise, promote and support GP well-being, and a sustainable primary care workforce.